1997
DOI: 10.1002/(sici)1097-0185(199712)249:4<469::aid-ar6>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic, juvenile, and adult development of the toadfish sonic muscle

Abstract: Immature muscle fibers formed embryonically in the larval period have a different morphology from immature fibers in adults, suggesting that splitting rather than SCs is a major source of new fibers in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…This is similar to the sciaenid Cynoscion (Ono and Poss, 1982) but contrasts with the toadfishes Porichthys and Opsanus and the tigerperch Therapon, which possess two triads at the A-I-band border (Eichelberg, 1976;Bass and Marchaterre, 1989;Loesser et al, 1997). However, the number of triads is not necessarily a taxonomic characteristic because both sciaenids and tigerperches (grunts) belong to the order Perciformes.…”
Section: Discussion Comparison Between Drumming Musclesmentioning
confidence: 76%
See 2 more Smart Citations
“…This is similar to the sciaenid Cynoscion (Ono and Poss, 1982) but contrasts with the toadfishes Porichthys and Opsanus and the tigerperch Therapon, which possess two triads at the A-I-band border (Eichelberg, 1976;Bass and Marchaterre, 1989;Loesser et al, 1997). However, the number of triads is not necessarily a taxonomic characteristic because both sciaenids and tigerperches (grunts) belong to the order Perciformes.…”
Section: Discussion Comparison Between Drumming Musclesmentioning
confidence: 76%
“…Second, the ribbons of myofibrils are shorter and the contractile elements and sarcotubules appear to be less regularly arranged. Occasionally, stacks of membranes, similar to whorl bodies in toadfishes (Loesser et al, 1997), were found between myofibrils. These whorl bodies were continuous with the SR. Third, the sarcomere length was significantly shorter than in sonic muscles (1.6 vs. 2.2. m).…”
Section: Musculus Tensor Tripodismentioning
confidence: 99%
See 1 more Smart Citation
“…According to Orlov et al, (1989), the fusion-associated vesicles are always present below the plasmalemma of more advanced myogenic cells (Loesser et al, 1997). In fishes, fusion-associated vesicles have been observed during myogenesis in O. mykiss (Nag and Nurse, 1972), M. glutinosa (Sandset and Konrneliussen, 1978) and Th.…”
Section: Cells Involved In Myotomal Muscle Growthmentioning
confidence: 99%
“…Generally speaking, swimbladder sounds have a fundamental frequency ranging from 75 to 300Hz, which would correspond to the muscle contraction rate, placing sonic muscles among the fastest in vertebrates (Rome et al, 1996;Loesser et al, 1997;Connaughton et al, 2000;Fine et al, 2001). The average dominant frequency of pulsed sounds in several carapid species varies between 40 and 340Hz (Parmentier et al, 2003;Lagardère et al, 2005;Parmentier et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%